Reconstruction of the ASN Managerial Position System: A Legal Study of the Merit System and Structural Anti-Corruption Strategy in ASN Law No. 20 of 2023 - Chaliati Dewi, Tutik Mahanani Umi; Virdaus, Saivol; Pratama, Topan Yulia (Borong Newinera Publisher, 2026)
This study aims to analyze the reconstruction of the State Civil Apparatus (ASN) position system from the perspective of administrative law as a strategy for preventing structural corruption, with a particular emphasis on the provisions of Law Number 20 of 2023 on ASN. The research employs a normative juridical method with statutory and conceptual approaches, supported by literature reviews and institutional reports. The analysis is grounded in administrative law theory (principles of legality, accountability, and merit), the rule of law, good governance, and structural anti-corruption theory. The findings reveal that although the merit system is normatively accommodated in Articles 13–18, its implementation continues to face serious deviations, including political interference, weak evaluation mechanisms, and the absence of clear rules on term limits. These conditions perpetuate bureaucratic patronage and create opportunities for structural corruption. This study proposes four reconstructive measures: (1) the issuance of implementing regulations concerning performance evaluation and term limitations; (2) the application of open merit-based assessments for all structural positions; (3) the institutional and executorial strengthening of the ASN Commission (KASN) and the National Civil Service Agency (BKN); and (4) the optimization of whistleblowing systems. These recommendations are expected to serve as legal and institutional instruments to strengthen the integrity, accountability, and professionalism of the bureaucracy, while closing loopholes for structural corruption in the governance of ASN positions.